POLARISASI OPINI DI MEDIA SOSIAL MENJELANG PEMILU TAHUN 2024 DI INDONESIA (LEMBAGA PUSAT KAJIAN KEBANGSAAN/PUSKAB UKRI, 2023)
The year 2024 is the year of the party as well as the stake of democracy in Indonesia, because in this year the presidential and legislative elections will be held. Ahead of the elections, the mainstream media and social media have provided many issues related to the 2024 elections so that the polarization of opinion in Indonesian society is getting stronger. This polarization divides the public into several groups supporting each candidate pair, namely groups supporting Anis-Muhaimin (AMIN), Prabowo-Gibran and Ganjar-Mahfud. This polarization is also supported by various efforts made by the three groups of candidate pairs, including the change movement carried by Anies-Muhaimin, continuing Jokowi's program carried by the Prabowo-Gibran candidate pair and accelerating towards superior Indonesia carried by the Ganjar-Mahfud candidate pair. However, there is a narrative being spread in the community related to the 2024 presidential election, namely dynastic politics, where it seems that there is an imposition of will from Jokowi to pass his son Gibran to become a vice presidential candidate to accompany Prabowo Subianto. This movement is very active in discussing and spreading narratives on social media. This study sought to explore and compare the polarization of opinions that developed in society through social media. This research uses a qualitative approach using the virtual ethnography method. The results show that the polarization of opinion that occurs on social media is not as significant as the polarization of opinion on social media.